2018
DOI: 10.1002/jwmg.21438
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing elk recruitment across ecotypes in the Western United States

Abstract: Ungulates are key components in ecosystems and economically important for sport and subsistence harvest. Yet the relative importance of the effects of weather conditions, forage productivity, and carnivores on ungulates are not well understood. We examined changes in elk (Cervus canadensis) recruitment (indexed as age ratios) across 7 states and 3 ecotypes in the northwestern United States during 1989-2010, while considering the effects of predator richness, forage productivity, and precipitation. We found a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 50 publications
2
44
1
Order By: Relevance
“…Throughout their range, elk occupy vastly different habitats where seasonal and regional differences in quality and quantity of nutritional resources vary as evident by autumn body fat of lactating females (Cook et al ). Additionally, assemblages and densities of carnivores vary throughout the range of elk, leading to variation in juvenile and adult survival (Griffin et al , Brodie et al , Lukacs et al ). These studies highlight the importance of understanding factors affecting population dynamics of elk at local and regional scales before embarking on management actions to improve productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout their range, elk occupy vastly different habitats where seasonal and regional differences in quality and quantity of nutritional resources vary as evident by autumn body fat of lactating females (Cook et al ). Additionally, assemblages and densities of carnivores vary throughout the range of elk, leading to variation in juvenile and adult survival (Griffin et al , Brodie et al , Lukacs et al ). These studies highlight the importance of understanding factors affecting population dynamics of elk at local and regional scales before embarking on management actions to improve productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, simultaneous investigations of climate and bottom‐up and top‐down forcing on prey populations are of greater utility than if examined separately. Increasingly more studies are attempting to assess the synergistic effects of these factors (Vucetich et al , Garrott et al , Melis et al , Johnson et al , Lukacs et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have demonstrated associations between NDVI and plant primary productivity and biomass (Tucker and Sellers 1986, Reed et al 1994, Thoma et al 2002, but less is known about the utility of NDVI for predicting the nutritional quality of ungulate forages, a key factor driving patterns of ungulate behavior and demography (Fryxell 1991, Tollefson et al 2011. Also, NDVI has been negatively associated with ground plant biomass in some habitat types (Borowik et al 2013), and summer NDVI has been negatively correlated with ungulate recruitment (Lukacs et al 2018) and abundance (Fauchald et al 2017). For example, higher NDVI is commonly assumed to reflect better forage conditions, but investigators have found that animals select for intermediate rather than high values of NDVI (Mueller et al 2008, Singh et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, elk are managed for their social importance (McCorquodale ), economic value (Fried et al , Schorr et al ), and diverse ecological effects (Kauffman et al , Mech ). Over the past several decades there has been a broad‐scale decline in elk recruitment across the western United States (Lukacs et al ). Concomitantly, wolves have become well established in many areas of the western United States since their reintroduction in 1995 (Jimenez et al ) and there is pressure for state wildlife management agencies to manage wolves to benefit ungulate populations.…”
mentioning
confidence: 99%